(untitled) (Journal of Partial Differential Equations, 2021)
In this paper, a class of nonhomogeneous Schrödinger-Poisson systems with strong singularity are considered. Combining with the variational method and Nehari method, we obtain a positive solution for this system which improves the recent results in the literature.